Human and mouse ZFP57 proteins are functionally interchangeable in maintaining genomic imprinting at multiple imprinted regions in mouse ES cells - Takikawa, Sachiko (Landes Bioscience, 2013)
Genomic imprinting is a common epigenetic phenomenon in mammals. Dysregulation of genomic imprinting has been implicated in a variety of human diseases. ZFP57 is a master regulator in genomic imprinting. Loss of ZFP57 causes loss of DNA methylation imprint at multiple imprinted regions in mouse embryos, as well as in embryonic stem (ES) cells. Similarly, mutations in human ZFP57 result in hypomethylation at many imprinted regions and are associated with transient neonatal diabetes and other human diseases. Mouse and human Zfp57 genes are located in the same syntenic block. However, mouse and human ZFP57 proteins only display about 50% sequence identity with different number of zinc fingers. It is not clear if they share similar mechanisms in maintaining genomic imprinting. Here we report that mouse and human ZFP57 proteins are functionally interchangeable. Expression of exogenous wild-type human ZFP57 could maintain DNA methylation imprint at three imprinted regions in mouse ES cells in the absence of endogenous mouse ZFP57. However, mutant human ZFP57 proteins containing the mutations found in human patients could not substitute for endogenous mouse ZFP57 in maintaining genomic imprinting in ES cells. Like mouse ZFP57, human ZFP57 and its mutant proteins could bind to mouse KAP1, the universal cofactor for KRAB zinc finger proteins, in mouse ES cells. Thus, we conclude that mouse and human ZFP57 are orthologs despite relatively low sequence identity and mouse ES cell system that we had established before is a valuable system for functional analyses of wild-type and mutant human ZFP57 proteins.